Ex-Situ Conservation Studies on Ethno-Medicinal Rare, Endemic Plant Species From Western Ghats of Maharashtra - DESHMUKH, B. S. (International Journal of Pharma and Bio Sciences, 2010)
Due to various factors such as changing environmental conditions, biotic factors, destruction of habitat etc. some ethno-medicinal rare endemic plant species are facing threats for their existence. Conservation, enhancement and sustainable utilization of plant resources are recognized as one of the vital segment in the natural resource management. The present work deals with the experience and efforts of promoting propagation and conservation of some selected plant species from of Western Ghats Maharashtra. Western Ghats region is one of the important Hot-spot of the world, situated in Sahyadri ranges of Maharashtra. The forest has great potentiality both from economic and botanical point of view. The endemic and medicinal plant species were abundant in this region and can be exploited due to improper management. Harvesting, grazing, shifting cultivation and uprooting of plant species for the purpose of food, fodder and medicines by tribal and local people are found the major cause for their threats. An extensive survey of Western Ghats region was carried out from ex-situ conservation point of view. Taxonomic, ecological and conservation aspects of selected ethno-medicinal rare, endemic plant species were studied. Ceropegia L., Dioscoria L., Gloriosa L. became rare due to habitat destruction and local consumption of tubers for food and medicine by rural communities. The endemic species of genus Smithia, Pinda, Pimpinella, Momordica and some important medicinal species of genus Chlorophytum, Rubia, Rauvolfia, Abrus, Hemidesmus, Mundulea and Cullen were identified with the help of standard literature and was studied. Seeds and propagating material were collected and propagated. Propagation through seed shows successful results. Transplantation through tubers requires similar ecological conditions. Well-drained soil, rich organic matter and sunny positions are good for Dioscoria L. Seeds of Gloriosa L. germinate well in wet and dumpy soil. Plants require rich organic soil and sunny situation. Live plants of all these species are maintained in healthy condition in botanical garden. Reasons for their threats and conservation measures were suggested.